PERAN GAYA KEPEMIMPINAN DAN PEKERJAAN DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR DINAS TENAGA KERJA KOTA BANJARMASIN - Kharunnisa (Jurnal Ilmiah Ekonomi Bisnis, 2020)
Formulation problem in this research are How leadership style and job to reach employee performance on Dinas Tenaga Kerja office in Banjarmasin city in this time. Aim are to knows leadership style and job to rearch employee performance on Dinas Tenaga Kerja office in Banjarmasin city in this time. Variance of data analysis are using descriptive quntitatif and qualitatif. Source of data are primer data and secunder data.Tekhnic data analysis is using discriptive quantitatif, so that easy to understood was using numeral.Technic unite data are using interview, observation and dokumentation. The population are 36 peoples based on ages, sex, marriage and education level. Performance indicators to consist of quality, quantity, presence and cooperation.